(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A strong partnership between homes and schools is crucial for the holistic development and success of students, particularly in the realm of language learning. When parents and educators collaborate effectively, they create a supportive environment that enhances language acquisition and proficiency. In this article, we explore the impacts of home-school partnerships on language learning and discuss practical strategies for fostering a successful collaboration.